2018
DOI: 10.1039/c7ra11577f
|View full text |Cite
|
Sign up to set email alerts
|

Many-body effects and non-local charge fluctuations in the double perovskite Sr2FeMoO6

Abstract: We studied the electronic structure of Sr2FeMoO6 using core level and valence band photoemission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…As a comparison, a different behavior of the screening mechanisms in the core-level and valence-band spectra was also observed in a double cluster model study on Sr 2 FeMoO 6 . While in the valence-band spectrum there is a clear signature of Fe-Mo nonlocal screening, the character of the Fe 2p and Mo 3p core-level peaks is similar to the ones obtained by single cluster model calculations [42], indicating that the interplay between two different TMO 6 octahedra depend on the ZSA [40] classification of each system.…”
Section: Screening Mechanisms and The Ti-ru Octahedra Interactionsupporting
confidence: 74%
See 1 more Smart Citation
“…As a comparison, a different behavior of the screening mechanisms in the core-level and valence-band spectra was also observed in a double cluster model study on Sr 2 FeMoO 6 . While in the valence-band spectrum there is a clear signature of Fe-Mo nonlocal screening, the character of the Fe 2p and Mo 3p core-level peaks is similar to the ones obtained by single cluster model calculations [42], indicating that the interplay between two different TMO 6 octahedra depend on the ZSA [40] classification of each system.…”
Section: Screening Mechanisms and The Ti-ru Octahedra Interactionsupporting
confidence: 74%
“…The reason for the differences may stem from the fact that both Ti 4+ and Ru 4+ ions favor the sharing of an O 2p electron, or in other words, the GS of the double perovskite is governed by charge-transfer configurations to such an extent that further ligand screening is not favorable. In a recent double cluster model calculation of Sr 2 FeMoO 6 [42], it was shown that the character of the Fe 2p and Mo 3p core-level peaks are mostly the same regardless of being calculated with double or single cluster models. In such a system, the Fe 3+ and Mo 5+ ions are classified within the chargetransfer ( < U ) and Mott-Hubbard ( > U ) regimes, respectively.…”
Section: Ti 2p and Ru 3p Core-level Spectramentioning
confidence: 99%
“…From previously reported double cluster calculations on SFMO, 20 the ground state was reported to be described by a mixed character of ionic 3d 5 as well as locally screened 3d 6 L and nonlocal 3d 6 v configurations, where v represent a hole in the valence band. The nonlocal screening involves an oxygen mediated Fe 3d−O 2p−Mo 4d hybridization.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…16−18 The complete ground-state electronic structure description in SFMO presents a more complex picture due to the large Fe−O and Mo−O hybridization as well as the importance of nonlocal Fe−O− Mo charge fluctuations. 19,20 This intricacy arises from the antiferromagnetic coupling between Fe and Mo sites, e.g., unlike the ferromagnetic coupling in manganites. In contrast to manganites like La 1−x Sr x MnO 3 , the strong local coupling in SFMO only applies to every other site since Mo is paramagnetic.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation